2004
DOI: 10.1093/ps/83.6.977
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effects of Dietary Lysine and Total Sulfur Amino Acid Level on Egg Production Parameters and Egg Components in Dekalb Delta Laying Hens

Abstract: Dekalb Delta hens were randomly assigned to one of eight dietary treatment groups. Two intakes of lysine (860 and 959 mg/hen per day) and 4 intakes of TSAA (635, 689, 811, 877 mg/hen per day) were combined in a 2 x 4 factorial treatment arrangement and fed from 20 to 43 wks of age. A phase feeding regimen was implemented at 43 wk with lysine intake lowered to 715 or 816 mg/hen per day and TSAA to 578, 607, 699, or 779 mg/hen per day. Cage was the experimental unit (5 hens/cage), and dietary treatments were rep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
72
4
27

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(124 citation statements)
references
References 6 publications
21
72
4
27
Order By: Relevance
“…Therefore, this result can be associated to the amino acid imbalance with the decreasing feed intake that might have negatively affected the intake of nutrients (calcium, phosphorus, vitamins, trace minerals and others) essential for egg shell formation. In contrast to the present result, Liu et al (2005) and Novak et al (2004) found no differences in egg shell percentage with increasing lysine levels in the diet.…”
Section: Resultscontrasting
confidence: 99%
“…Therefore, this result can be associated to the amino acid imbalance with the decreasing feed intake that might have negatively affected the intake of nutrients (calcium, phosphorus, vitamins, trace minerals and others) essential for egg shell formation. In contrast to the present result, Liu et al (2005) and Novak et al (2004) found no differences in egg shell percentage with increasing lysine levels in the diet.…”
Section: Resultscontrasting
confidence: 99%
“…De acordo com Novak et al (2004), a síntese de proteína no tecido do magno pode ser afetada por mudanças na concentração de aminoácidos no sangue. Porém, o aumento da ingestão de metionina + cistina digestível no presente estudo não aumentou a porcentagem de albúmen (P>0,05), embora tenha aumentado o peso médio do albúmen, que variou de 35,4 a 38, 5 g A redução na porcentagem de casca pode ser devido ao aumento verificado no tamanho dos ovos, sem aumento na produção da casca.…”
Section: Resultsunclassified
“…Resultados semelhantes ao do presente estudo foram obtidos por Novak et al (2004) ao trabalharem com poedeiras leves de 44 a 63 semanas de idade, com consumos de aminoácidos sulfurosos que variaram de 615 a 833 mg/ave/ dia, verificando efeito significativo para porcentagem de gema e não significativo para porcentagem de albúmen. Por outro lado, Pavan et al (2005), trabalhando poedeiras semipesadas e consumos que variaram de 661 a 823 mg/ave/ dia de aminoácidos sulfurosos, constataram efeito significativo tanto para percentual de gema quanto para percentual de albúmen.…”
Section: Resultsunclassified
“…Zootec., v.67, n.6, p.1675-1683, 2015 Prochaska et al (1996) avaliaram a influência da ingestão de rações com três níveis de lisina (677; 1.154 e 1.613mg/ave/dia) sobre os componentes dos ovos (sólidos do albúmen, sólidos de gema, proteína do albúmen e proteína da gema) de poedeiras de 42 a 64 semanas de idade e detectaram efeito significativo nas variáveis avaliadas, de modo que o maior nível de ingestão de lisina promoveu a maior resposta desses componentes. Novak et al (2004) também observaram aumento significativo no percentual de albúmen dos ovos de poedeiras alimentadas com 959mg de lisina total/ave/dia em comparação aos ovos das aves alimentas com 860mg de lisina total/ave/dia, e esse aumento se refletiu diretamente no percentual de sólidos do albúmen.…”
Section: Methodsunclassified